2018
DOI: 10.1080/01431161.2018.1490503
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric calibration framework for ultra-high-resolution UAV-derived orthomosaics for large-scale mapping of invasive alien plants in semi-arid woodlands:Harrisia pomanensisas a case study

Abstract: Orthomosaics derived from consumer grade digital cameras on board unmanned aerial vehicles (UAVs) are increasingly being used for biodiversity monitoring and remote sensing of the environment. To have lasting quantitative value, remotely sensed imagery should be calibrated to physical units of reflectance. Radiometric calibration improves the quality of raw imagery for consistent quantitative analysis and comparison across different calibrated imagery. Moreover, calibrating remotely sensed imagery to units of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 49 publications
3
38
0
Order By: Relevance
“…Flight altitudes of small UAS (sUAS) typically do not exceed 250 meters due to governmental restrictions on UAS operations [34]. As a result, numerous UAS studies have implemented an empirical line method (ELM) for radiometric calibration of UAS imagery [35,36,[45][46][47][37][38][39][40][41][42][43][44]. The foundation of an ELM is the regression of ground-based spectroradiometer measurements and airborne remotely sensed measurements of a spectrally stable calibration target to develop calibration equations that convert image digital numbers (DNs) to physical at-surface reflectance units [48].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Flight altitudes of small UAS (sUAS) typically do not exceed 250 meters due to governmental restrictions on UAS operations [34]. As a result, numerous UAS studies have implemented an empirical line method (ELM) for radiometric calibration of UAS imagery [35,36,[45][46][47][37][38][39][40][41][42][43][44]. The foundation of an ELM is the regression of ground-based spectroradiometer measurements and airborne remotely sensed measurements of a spectrally stable calibration target to develop calibration equations that convert image digital numbers (DNs) to physical at-surface reflectance units [48].…”
Section: Introductionmentioning
confidence: 99%
“…For example, using nine near-Lambertian calibration targets, Wang and Myint [40] found an exponential relationship between their consumergrade sensor-recorded digital numbers (DNs) and ground-based spectroradiometer reflectance. Following the simplified ELM radiometric calibration framework recommended by Wang and Myint [40], Mafanya et al [45] found that using a calibration target with six gray levels could quantify this nonlinear relationship and produced an accurate image calibration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of this correction is to reduce errors in the acquired digital values of the pixels due to atmospheric or sensor factors [46]. This process is fundamental when dealing with images acquired from different sensors or on different days [47]. Additionally, radiometric correction may involve converting digital numbers to physical units [48].…”
Section: Introductionmentioning
confidence: 99%